1997
DOI: 10.1046/j.1469-0705.1997.09030173.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐vessel view of the fetal upper mediastinum: an easy means of detecting abnormalities of the ventricular outflow tracts and great arteries during obstetric screening

Abstract: The three-vessel view is a transverse view of the fetal upper mediastinum is as simple to obtain as the four-chamber view. It demonstrates the main pulmonary artery, ascending aorta and superior vena cava in cross- or oblique sections. The purposes of this study were to describe the normal anatomy of the three-vessel view and to analyze what anatomical changes would occur in this view when there are lesions of the ventricular outflow tracts and/or great arteries. Sonograms of 29 fetuses with lesions involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
233
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(255 citation statements)
references
References 0 publications
6
233
0
7
Order By: Relevance
“…In our study, all cases with right aortic or double arches showed an abnormal axial, upper, mediastinal view with U-shaped intermediate trachea. Although a similar upper-mediastinal view has been recently described 13 , and even suggested to be incorporated in a sequential segmental approach to fetal congenital heart disease 14 , no indication for tracheal identification or linkage with aortic arch anomalies has been mentioned. We therefore recommend that the trachea be added as a landmark in evaluation of the aortic arch while performing fetal cardiac examination.…”
Section: Figure 4 Longitudinal View Showing Kommerell's Diverticulum mentioning
confidence: 99%
“…In our study, all cases with right aortic or double arches showed an abnormal axial, upper, mediastinal view with U-shaped intermediate trachea. Although a similar upper-mediastinal view has been recently described 13 , and even suggested to be incorporated in a sequential segmental approach to fetal congenital heart disease 14 , no indication for tracheal identification or linkage with aortic arch anomalies has been mentioned. We therefore recommend that the trachea be added as a landmark in evaluation of the aortic arch while performing fetal cardiac examination.…”
Section: Figure 4 Longitudinal View Showing Kommerell's Diverticulum mentioning
confidence: 99%
“…However, the diagnostic accuracy for prenatal diagnosis of congenital heart disease is limited . Reasons for the low detection rates include: (1) inadequate examination; (2) anomalies not present at the time of routine ultrasound scan (e.g., valvular disorders may evolve during pregnancy); and (3) incomplete evaluation of the outflow tracts [9,10,[37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…An isolated enlarged coronary sinus (Figure 5) is highly suggestive of persistent LSVC, although this finding may have both false positive and false negative diagnoses 3 28 35 …”
Section: Discussionmentioning
confidence: 99%